PERSEPSI PESERTA DIDIK TENTANG PEMBELAJARAN DARING MATA PELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DI SMP (SLUB) SARASWATI 1 DENPASAR - Ayu Kadek Tri Bhuana; I Made Wiguna Yasa; Ni Nyoman Mariani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Abstract The COVID-19 pandemic has affected all aspects of life, including the world of education, especially Hindu religious education and Moral. Based on this, researchers are interested in knowing the perceptions of students about online learning for Hindu Religion and Moral subjects at SMP (SLUB) Saraswati 1 Denpasar. This type of research is survey research using a quantitative approach. The population in this study were all 7th grade students who were Hindu, totaling 227 students. The sampling technique used is simple random sampling technique totaling 69 students. The research instrument used was a questionnaire with 22 statements. All statement items are declared valid and reliable. Data analysis was performed using descriptive statistics, namely by determining the lowest score, highest score, ideal mean (Mi) and ideal standard deviation (SDi. The results showed that the perception of students towards online learning in the subjects of Hindu Religion and Moral subjects as many as 22 respondents (31.88%) had a very good perception, 25 respondents (36.23%) had a good perception, 21 respondents (30.43%) have a sufficient perception, 1 respondent (1.45%) has a bad perception, and no respondent has a very bad perception. Based on the results of the study, the students' perceptions of online learning in the subjects of Hindu Religion and Moral Education are mostly good. Keywords: Online Learning, Hindu Religious Education and Moral Subjects